Microbiologically documented infection and antimicrobial sensitivities in pediatric malignancy patients with febrile neutropenia at Dr Saiful Anwar Hospital, Malang, Indonesia - Savitri Laksmi Winaputri; Dominicus Husada; Budi Utomo; Irene Ratridewi; Susanto Nugroho; I Dewa Gede Ugrasena; Parwati Setiono Basuki; Ismoedijanto Ismoedijanto (Jurnal Kedokteran Syiah Kuala, 2020)
Abstract. Background: Febrile neutropenia in malignancy children increase the risk of infection, morbidity and mortality. Microbiologically documented infection in pediatric malignancy has not been studied in Saiful Anwar Hospital. Purpose: Determine profile of blood, urine, sputum, and wound bed culture and antimicrobial sensitivities pattern in pediatric malignancy patients with febrile neutropenia. Methods: Pediatric malignancy patients with febrile neutropenia and microbiologically documented infection admitted to dr Saiful Anwar General Hospital Malang, were studied from 2016 to 2019.  Bacterial and fungal etiology were identified, along with antimicrobial sensitivities patterns. Results: 53 (17%) of 307 pediatric malignancy patients with febrile neutropenia experienced 75 episodes of microbiologically documented infection. 40 (53,3%) gram-negative and 34 (45,3%) gram-positive isolated from 75 isolated pathogens. The most common gram-negative were Klebsiella pneumonia (n=15) and Escherichia coli (n=8). The most common gram-positive were Coagulase-negative Staphylococci (n=14) and Enterococcus faecalis (n=7). Escherichia coli, Coagulase-negative Staphylococci, Enterococcus faecalis, and Staphylococcus aureus were 100% sensitive to all tested antimicrobials. Klebsiella pneumonia and Acinetobacter baumanni were 100% sensitive to almost all tested antimicrobials. Pseudomonas aeruginosa was found less sensitive (0-80%) to all tested antimicrobials. Conclusion: Investigation of antimicrobial sensitivities of these organisms may guide successful antimicrobial therapy and improve quality of pediatric malignancy care. Abstrak. Latar Belakang: Demam neutropenia pada keganasan anak meningkatkan risiko infeksi, morbiditas dan mortalitas. Microbiologically Documented Infection merupakan masalah utama di dunia, namun belum dilakukan penelitian di RSUD Dr. Saiful Anwar. Tujuan: Melihat gambaran kultur darah, urine, sputum, dan dasar luka dan pola sensitivitas antimikroba pada keganasan anak dengan demam neutropenia. Metode: Pasien keganasan anak dengan demam neutropenia di bangsal Hemato-onkologi Departemen Ilmu Kesehatan Anak RSUD Dr. Saiful Anwar Malang dan terdiagnosis Microbiologically Documented Infection pada tahun 2016-2019, ditentukan etiologi, serta pola sensitivitas antimikroba. Hasil: Dari 307 pasien keganasan anak dengan demam neutropenia, 53(17%) pasien mengalami 75 episode microbiologically documented infection. Didapatkan 40(53,3%) bakteri gram negatif dan 34(45,3%) gram positif dari 75 hasil kultur. Bakteri gram negatif yang paling banyak ditemukan adalah Klebsiella pneumonia (n=15) dan Escherichia coli (n=8), serta Coagulase-negative Staphylococci (n=14) dan Enterococcus faecalis (n=7) pada gram positif. Escherichia coli, Coagulase-negative Staphylococci, Enterococcus faecalis, dan Staphylococcus aureus 100% sensitif terhadap semua antimikroba yang diuji. Klebsiella pneumonia dan Acinetobacter baumanni 100% sensitif terhadap hampir semua anitmikroba yang diuji. Pseudomonas aeruginosa memiliki sensitivitas rendah (0-80%) terhadap semua antimikroba yang diuji. Kesimpulan: Penelitian tentang sensitivitas antimikroba pada organisme tersebut dapat menjadi panduan untuk keberhasilan terapi dan meningkatkan kualitas pelayanan pada keganasan anak.